The Game Theory, Morality and the ‘Game of Life’ - Das, Amaresh; Alemayehu, Biruk (Journal of Asian Business Strategy, 2013)
Game theory as long as it is a study of interdependent rational choice, can be used to explain, to predict and evaluate human behavior in contexts where the outcome of action depends on what other agents choose to do. Game theory can be made relevant to ethics and can be used in moral and political philosophy, including economics, business and public policy areas.